A degradable fly ash oil-water interface separator and its preparation method and application

By using fly ash and other materials, the degradable fly ash oil water interface partitions are solved, and the existing technology has reduced its effect in high-temperature and high-salt environments are achieved, efficient water blocking and controllable degradation are achieved, and the oil field formation environment is protected.

CN116606117BActive Publication Date: 2025-04-25YANGTZE UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310515009.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-04
Publication Date
2025-04-25
Estimated Expiration
2043-05-04

AI Technical Summary

Technical Problem

The existing oilfield water blocking technology has decreased its effect in high temperature and high salt environments, and is cost-effective, has a small sealing strength, and is non-degradable, affecting the formation environment.

Method used

A degradable fly ash oil water interface partition consisting of fly ash, polymer aluminum chloride, urea, N,N-dimethacrylamide/acryloylmorpholine binary polymer and silica sol is used to form a water blocking system suspended at the oil-water interface through the solid-liquid interface diffusion double layer theory and complex control ion equilibrium method.

Benefits of technology

The water blocking effect is achieved with significant compressive strength and temperature resistance and salt resistance in high-temperature and high-salt environments. At the same time, the partition density is adjustable, which can degrade in a strong acid environment and protect the formation environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116606117B_ABST
    Figure CN116606117B_ABST
Patent Text Reader

Abstract

The present invention discloses a degradable fly ash oil-water interface partition and its preparation method and application. The partition is composed of the following raw materials in parts by weight: 10-20 parts of fly ash, 20-30 parts of polyaluminium chloride, 3-5 parts of urea, 2-4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5-1 parts of silica sol, and the balance is water, and the sum of the parts by weight of the above components is 100. The water blocking system of the present invention is easy to prepare, has a wide source of raw materials, good injectability, simple construction process, and low cost, and can automatically spread at the oil-water interface; before curing, it has high viscosity and resistance to dilution, and has the advantage of "right-angle curing"; after curing, the compressive strength of the partition is greatly increased; at the same time, the partition has strong heat and salt resistance, and the partition density is 1.05-1.13g / cm 3 It is adjustable and controllable, and can be degraded in a strong acid environment, which is beneficial to protecting the formation environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a degradable fly ash oil-water interface separator and a preparation method and application thereof. Background Art

[0002] Cavernous oil reservoirs are widely distributed in the world. The reservoirs are highly heterogeneous, and the oil-water storage state and connectivity are complex. The difficulty of water plugging technology is much higher than that of conventional sandstone reservoirs and other carbonate reservoirs. Artificial baffle water plugging methods may be the most effective water plugging method at present. Artificial baffles built in the formation can be used to plug specific water outlet locations.

[0003] At present, the commonly used plugging agents in oil fields are polymer gel, precipitation type plugging agent and conventional cement. Polymer gel will dissolve under high temperature and high salt formation conditions, and the solution viscosity is large, and the pumping resistance is large; the precipitation type plugging agent has low strength; conventional cement is easy to leak and has a small plugging radius; therefore, conventional plugging technology is not suitable for high temperature and high mineralization fracture-cavity oil reservoirs.

[0004] CN202010997784.5 discloses a density selective water plugging system for cave oil reservoirs. The plugging agent system comprises, by weight, 50-75 parts of super absorbent resin, 100-150 parts of ultrafine curable particles, 42-50 parts of microsilicon, 5-10 parts of dispersant, 1-5 parts of retarder, and 1000-1200 parts of formation water; the super absorbent resin is a hydrophilic and lipophilic absorbent resin with a volume expansion multiple greater than a specific threshold; the overall density of the water plugging system is 1.05-1.14 g / cm 3. The oil-water interface spreads in the cave, and then gradually solidifies, forming a baffle at the oil-water interface, establishing a shield, adjusting the flow field, controlling the flow of the lower water body, and achieving the purpose of reducing water and increasing oil. The density of the system is adjustable, the compressive strength is moderate, and the water plugging effect is obvious. However, in a high temperature and high salt environment, the water plugging effect is significantly reduced, and it is not degradable. CN201210247170.0 discloses a carbonate oil well density selective water plugging agent, and its component formula is calculated by weight, 100 parts of cement, 60-75 parts of fly ash, 50-58 parts of clay, 52-62 parts of microsilicon, 5-8 parts of early strength agent, 16-28 parts of fluid loss agent, and 1100-1200 parts of water. Stay between the oil-water interface, establish a water plugging baffle, and ensure the solidification effect. The plugging agent has strong compressive strength and obvious water plugging effect, but in a high temperature and high salt environment, the water plugging effect is significantly reduced, and it is not degradable. CN201610296608.2 discloses a polysaccharide polymer water plugging gel, which is composed of the following components in mass percentage: 2.5% to 5% polysaccharide main agent, 1% to 2% cross-linking agent, 1% to 3% cosolvent, 0% to 10% gelling regulator, and the rest is water, and the total of the components is 100%. The gel system has a wide temperature application range and can be used for both high-temperature oil reservoir water plugging operations and low-temperature oil reservoir water plugging operations; the final setting strength can reach visual code level I; it has good long-term stability; and the gel system is biodegradable. However, the effect of the system in a high-mineralization environment is significantly reduced. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a degradable fly ash oil-water interface partition and its preparation method and application, and solve the technical problems of high cost, low plugging strength, unsuitability for ultra-high temperature and high salt reservoirs and non-degradability of the water plugging system in the prior art.

[0006] In a first aspect, the present invention provides a degradable fly ash oil-water interface separator, which is composed of the following raw materials in parts by weight: 10-20 parts of fly ash, 20-30 parts of polyaluminum chloride, 3-5 parts of urea, 2-4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5-1 part of silica sol, and the balance is water, and the sum of the parts by weight of the above components is 100.

[0007] In a second aspect, the present invention provides a method for preparing a degradable fly ash oil-water interface separator, comprising the following steps:

[0008] Fly ash, polyaluminium chloride, urea, N,N-dimethylacrylamide / acryloylmorpholine binary polymer, silica sol and water are uniformly mixed and then cured to obtain a degradable fly ash oil-water interface separator.

[0009] In a third aspect, the present invention provides an application of a degradable fly ash oil-water interface separator, wherein the degradable fly ash oil-water interface separator is applied to water plugging in oil fields.

[0010] Compared with the prior art, the present invention has the following beneficial effects:

[0011] The present invention is based on the double-layer diffusion theory of the solid-liquid interface, combined with methods such as complexation to control ion balance, to form a water plugging system suspended at the oil-water interface; the water plugging system of the present invention is easy to prepare, has a wide source of raw materials, good injectability, simple construction process, low cost, can automatically spread at the oil-water interface, and then gradually solidify to form a partition at the oil-water interface; before solidification, it has high viscosity and resistance to dilution, and has the advantages of "right-angle solidification"; after solidification, the compressive strength is 1.2MPa-6.8MPa, and the maximum plugging pressure gradient can reach 86MPa / m, which greatly increases the compressive strength of the partition; at the same time, the partition has strong heat and salt resistance, the temperature resistance can reach above 170°C, and the salt resistance can reach above 250000mg / L, achieving a new breakthrough in the heat and salt resistance of the granular self-solidifying plugging agent; the density of the partition is 1.05-1.13g / cm 3 It is adjustable and controllable, and can be degraded in a strong acid environment, which is beneficial to protecting the formation environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The mass variation trend of the degradable fly ash oil-water interface partition of Examples 1-3 of the present invention with temperature;

[0013] Figure 2 The quality of the degradable fly ash oil-water interface separator of Examples 1-3 of the present invention varies with the mineralization degree;

[0014] Figure 3 The quality change trend of the degradable fly ash oil-water interface separator of Examples 1-3 of the present invention under strong acid and high temperature conditions;

[0015] Figure 4 The stress-strain curves of the degradable fly ash oil-water interface separators of Example 2 of the present invention and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0017] In a first aspect, the present invention provides a degradable fly ash oil-water interface separator, which is composed of the following raw materials in parts by weight: 10-20 parts of fly ash, 20-30 parts of polyaluminum chloride, 3-5 parts of urea, 2-4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5-1 part of silica sol, and the balance is water, and the sum of the parts by weight of the above components is 100.

[0018] In the present invention, fly ash is used as the main body, and urea and silica sol are used as curing agents. Polyaluminium chloride and urea form gel through hydration; fly ash is charged because it is a particle, and forms a stable skeleton material through hydrogen bonding; N,N-dimethylacrylamide / acryloylmorpholine binary polymer has high temperature thixotropy, and after being added, the whole becomes a thixotropic skeleton material, so that the partition has excellent salt resistance and temperature resistance, and is conducive to further improving the compressive strength of the partition; in addition, the addition of silica sol has a strengthening effect, making the whole more stable. The present invention can achieve a partition density of 1.05-1.13g / cm by selecting the proportion of raw materials. 3 Adjustable and controllable, it is conducive to the formation of partitions at the oil-water interface. In addition, the inventors found during the experiment that before the addition of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, the mixed liquid needs to be heated in an oven at 170°C for 4 hours to form a partition, and the maximum compressive strength after curing is 5.5MPa; after adding the polymer, it only takes 3 hours to form a partition, and the maximum compressive strength of the partition curing is 6.8MPa. It can be seen that the addition of N,N-dimethylacrylamide / acryloylmorpholine binary polymer can also shorten the curing time and improve the curing effect.

[0019] In the present invention, the fly ash used is a major by-product of coal resource utilization. Before use, the fly ash can be subjected to impurity removal, washing and drying treatments in sequence as required.

[0020] In this embodiment, the N,N-dimethylacrylamide / acryloylmorpholine binary polymer is obtained by mixing N,N-dimethylacrylamide and acryloylmorpholine and reacting them under the action of an initiator. The mass ratio of N,N-dimethylacrylamide to acryloylmorpholine is 1:(0.5-2), further 1:1; the initiator is ammonium persulfate, and the amount of the initiator added accounts for 0.05%-0.1% of the monomer mass; the reaction temperature is 40-55°C, and the reaction time is 2-3h.

[0021] In this embodiment, the content of silicon dioxide in the silica sol is 20-40%; the basicity of polyaluminium chloride is 40-90%; and the content of aluminium oxide is 10-32%.

[0022] In some specific embodiments of the present invention, the degradable fly ash oil-water interface separator is composed of the following raw materials in parts by weight: 15 parts of fly ash, 25 parts of polyaluminum chloride, 4 parts of urea, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5 parts of silica sol, and the balance is water. The sum of the parts by weight of the above components is 100.

[0023] In a second aspect, the present invention provides a method for preparing a degradable fly ash oil-water interface separator, comprising the following steps:

[0024] Fly ash, polyaluminium chloride, urea, N,N-dimethylacrylamide / acryloylmorpholine binary polymer, silica sol and water are uniformly mixed and then cured to obtain a degradable fly ash oil-water interface separator.

[0025] In this embodiment, the curing temperature is 150-200° C., further 170° C.; the curing time is 2-6 hours, further 3 hours.

[0026] In a third aspect, the present invention provides an application of a degradable fly ash oil-water interface separator, wherein the degradable fly ash oil-water interface separator is applied to water plugging in oil fields.

[0027] To avoid redundancy, some of the raw materials in the following embodiments of the present invention are summarized as follows:

[0028] Polyaluminium chloride: High-purity polyaluminium chloride produced by Airfoc, with a basicity of 90% and an alumina content of 30%;

[0029] Silica sol: Shandong Better New Materials Co., Ltd., silica content 30%;

[0030] N,N-dimethylacrylamide / acryloylmorpholine binary polymer: N,N-dimethylacrylamide and acryloylmorpholine are mixed at a mass ratio of 1:1, and 0.08% of ammonium persulfate by mass of the monomer is added, stirred and heated to 50° C., reacted for 2 hours and then cooled to obtain.

[0031] Example 1

[0032] (1) 20 parts of fly ash, 30 parts of polyaluminium chloride, 4 parts of urea, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5 parts of silica sol, and the balance of water, the sum of the weight parts of the above components being 100, are mixed;

[0033] (2) After being fully dissolved, the mixture is placed in an oven at 170°C and heated for 3 hours to form a degradable fly ash oil-water interface partition.

[0034] Example 2

[0035] (1) 15 parts of fly ash, 25 parts of polyaluminium chloride, 4 parts of urea, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5 parts of silica sol, and the balance of water, the sum of the weight parts of the above components being 100, are mixed;

[0036] (2) After being fully dissolved, the mixture is placed in an oven at 170°C and heated for 3 hours to form a degradable fly ash oil-water interface partition.

[0037] Example 3

[0038] (1) 10 parts of fly ash, 20 parts of polyaluminium chloride, 4 parts of urea, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5 parts of silica sol, and the balance of water, the sum of the weight parts of the above components being 100, are mixed;

[0039] (2) After being fully dissolved, the mixture is placed in an oven at 170°C and heated for 3 hours to form a degradable fly ash oil-water interface partition.

[0040] Comparative Example 1

[0041] (1) 15 parts of fly ash, 25 parts of polyaluminium chloride, 4 parts of urea, 0.5 parts of silica sol and the balance of water are mixed, the sum of the weight parts of the above components being 100;

[0042] (2) After being fully dissolved, the mixture is placed in a 170°C oven and heated for 4 hours to form a degradable fly ash oil-water interface partition.

[0043] Comparative Example 2

[0044] (1) 15 parts of fly ash, 25 parts of polyaluminium chloride, 4.5 parts of urea, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, and the balance of water, the sum of the weight parts of the above components being 100, are mixed;

[0045] (2) After being fully dissolved, the mixture is placed in an oven at 170°C and heated for 3 hours to form a degradable fly ash oil-water interface partition.

[0046] Comparative Example 3

[0047] (1) 15 parts of fly ash, 25 parts of polyaluminium chloride, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 4.5 parts of silica sol, and the balance of water, the sum of the weight parts of the above components being 100, are mixed;

[0048] (2) After being fully dissolved, the mixture is placed in an oven at 170°C and heated for 3 hours to form a degradable fly ash oil-water interface partition.

[0049] Experimental Group 1

[0050] The partitions formed in Examples 1-3 were placed in equal portions in a drying oven at 25°C, 50°C, 70°C, 90°C, 110°C, 130°C, 150°C, and 170°C for 24 hours, and the quality of the partitions was measured. Figure 1 shown.

[0051] See also Figure 1 ,pass Figure 1 It can be seen that the quality of the partition formed in Example 2 is moderate, and as the temperature increases, the quality of the partitions formed in Examples 1-3 remains basically unchanged, indicating that the oil-water interface partitions provided by the present invention have good temperature resistance.

[0052] Experimental Group 2

[0053] The separators formed in Examples 1-3 were placed in equal portions into aqueous solutions with mineralizations of 100000 mg / L, 150000 mg / L, 200000 mg / L, and 250000 mg / L, respectively, and then placed in a drying oven at 90°C for 12 hours. The final mass of the separators was measured. Figure 2 shown.

[0054] See also Figure 2 ,pass Figure 2 It can be seen that the quality of the separator formed in Example 2 is moderate, and as the mineralization increases, the quality of the separators formed in Examples 1-3 remains basically unchanged, indicating that the oil-water interface separators provided by the present invention have good salt resistance.

[0055] Experimental Group 3

[0056] The separators formed in the above Examples 1-3 were respectively mixed with a sufficient amount of conventional earth acid solution (3% HF + 12% HCl), and heated in an oil bath at 110° C. for 8 h. The quality of the final separators was measured. Figure 3 shown.

[0057] See also Figure 3 ,pass Figure 3 It can be seen that the partitions formed in Examples 1-3 are easily degraded under the action of strong acid and high temperature environment, indicating that the oil-water interface partitions provided by the present invention have significant degradation ability under the action of strong acid in the formation environment.

[0058] Experimental Group 4

[0059] The separators formed in Example 2 and Comparative Examples 1-3 were respectively placed in a compressive strength tester to record the stress-strain curves of the separators. Figure 4 shown.

[0060] See also Figure 4 ,pass Figure 4It can be seen that after omitting the binary copolymer (Comparative Example 1), omitting the silica sol (Comparative Example 2), and omitting the urea (Comparative Example 3), the compressive strength of the formed partition is reduced to varying degrees, indicating that in the system of the present invention, the binary copolymer, silica sol, and urea can play their synergistic role and significantly improve the compressive strength of the partition.

[0061] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A degradable fly ash oil-water interface separator, characterized in that: The degradable fly ash oil-water interface separator is composed of the following raw materials in parts by weight: 10-20 parts of fly ash, 20-30 parts of polyaluminium chloride, 3-5 parts of urea, 2-4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5-1 part of silica sol, and the balance is water, the sum of the parts by weight of the above components being 100; wherein, The N,N-dimethylacrylamide / acryloylmorpholine binary polymer is obtained by mixing N,N-dimethylacrylamide and acryloylmorpholine in a mass ratio of 1:(0.5-2) and reacting them under the action of an initiator.

2. The degradable fly ash oil-water interface separator according to claim 1, characterized in that: The content of silicon dioxide in the silica sol is 20-40%.

3. The degradable fly ash oil-water interface separator according to claim 1, characterized in that: The basicity of the polyaluminium chloride is 40-90%, and the content of aluminium oxide is 10-32%.

4. The degradable fly ash oil-water interface separator according to claim 1, characterized in that: The initiator is ammonium persulfate, and the amount of the initiator added is 0.05%-0.1% of the monomer mass; the reaction temperature is 40-55° C., and the reaction time is 2-3 hours.

5. The degradable fly ash oil-water interface separator according to claim 1, characterized in that: The degradable fly ash oil-water interface separator is composed of the following raw materials in parts by weight: 15 parts of fly ash, 25 parts of polyaluminium chloride, 4 parts of urea, 4 parts of N,N-dimethylacrylamide / acryloylmorpholine binary polymer, 0.5 parts of silica sol, and the balance is water, and the sum of the parts by weight of the above components is 100.

6. A method for preparing the degradable fly ash oil-water interface separator according to any one of claims 1 to 5, characterized in that: The following steps are involved: Fly ash, polyaluminium chloride, urea, N,N-dimethylacrylamide / acryloylmorpholine binary polymer, silica sol and water are uniformly mixed and then cured to obtain a degradable fly ash oil-water interface separator.

7. The method for preparing the degradable fly ash oil-water interface separator according to claim 6, characterized in that: The curing temperature is 150-200° C., and the curing time is 2-6 hours.

8. The method for preparing the degradable fly ash oil-water interface separator according to claim 6, characterized in that: The curing temperature is 170° C., and the curing time is 3 hours.

9. An application of the degradable fly ash oil-water interface separator as claimed in any one of claims 1 to 5, characterized in that: The degradable fly ash oil-water interface separator is used for water plugging in oil fields.

Citation Information

Patent Citations

  • Carbonatite oil well density selectivity water shutoff agent and preparation process thereof

    CN102746835A

  • A kind of polysaccharide polymer hydroblocking gel

    CN105754566B

  • A density selective water plugging system for cave oil reservoirs and preparation method thereof

    CN114427375B

  • Inorganic gel foam water shutoff profile control agent for low-permeability oil reservoir

    CN105586023A

  • Oil field reservoir large pore path or extra-high permeable band blocking agent and preparation method thereof

    CN106967403A